William S. Burroughs [videorecording (DVD)] : a man within - Leyser, Yony; Weller, Peter, 1947-; Waters, John, 1946-; Smith, Patti; Pop, Iggy, 1947- (Oscilloscope Laboratories, 2011)
An in-depth look at the troubled and brilliant world of American author William S. Burroughs, one of the first writers to cross the boundaries of queer and drug culture in the 1950s. Features never-before-seen archival footage and exclusive interviews with colleagues and confidants including John Waters, Patti Smith, Iggy Pop, Gus Van Sant, Genesis Breyer P-Orridge, Thurston Moore, Lee Ranaldo, Laurie Anderson, Amiri Baraka, Jello Biafra, and David Cronenberg.